Characterisation of climatic variables used to identify instability thresholds in clay slopes. Issue 3 (26th September 2018) - Pedone, G.; Ruggieri, G.; Trizzino, R.
Abstract : The paper reports the results of a slope-atmosphere interaction analysis performed with reference to geo-hydro-mechanical conditions typically observed on the Southern Apennines (Italy). The aim of the analysis is to gain some understanding in the characterisation of climatic variables employed to identify instability thresholds in clay slopes. A seepage analysis was undertaken first, showing that Mediterranean climates can produce significant pore-pressure changes also at depths not usually considered to be affected by atmospheric conditions. Based on the results of the seepage analysis, limit equilibrium analyses were carried out for a 5 m and a 20 m deep landslide, confirming that also deep movements in clay slopes can be related to slope-atmosphere interaction. The characterisation of climatic variables aimed at identifying instability thresholds is finally discussed based on the analyses reported in the paper. The results show that net rainfall cumulated over 2 and 6 months represent suitable climatic variables for the 5 m and the 20 m deep landslide, respectively. These findings suggest that the stability of a clay slope, when referred to shallow movements, is likely to depend on the rainfall infiltrating over a few weeks at least. When deep movements are considered, the stability seems to depend more on the rainfall gradually infiltrating during the most rainy seasons.